Master protocols in low- and middle-income countries: a review of current use, limitations and opportunities for precision medicine - Jingky Lozano-Kuehne; Shaun Hiu; James M S Wason; Theophile Bigirumurame; Luke O Ouma; Sarah Al-Ashmori; Samuel Sarkodie; Lou Whitehead; Ann Breeze Konkoth; Dorcas Njeri Kareithi; Marzieh Shahmandi (BMJ Global Health)
Background Master protocols—umbrella, basket and platform trials, study multiple therapies, multiple diseases or both, offering many advantages, most profoundly that they answer multiple treatment-related questions, which would otherwise take multiple trials. We conducted a review of clinical trial registries to characterise their use in advancing precision medicine in low and middle-income countries (LMICs).Methods We searched trial records available in 20 trial registries globally, including ClinicalTrials.gov and WHO ICTRP, to identify umbrella, basket and platform trials launched until 30 September 2023.Results We identified 102 master protocols—29 umbrella trials, 31 basket trials, 36 platform trials, as well as six other designs that partially aligned with the working definition of master protocols, run in 54 different LMICs. Most trials were pharmaceutical industry-sponsored studies (60/102, 58.8%), conducted in oncology settings (56/102, 54.9%), currently ongoing (69/102, 67.6%) in early phase (phase I and II) settings (70/102, 68.6%) and have been planned or launched in the last 5 years (93/102, 91.2%), mainly with international collaborations in high-income countries. China was a site to more than half of all master protocols (53/102, 52%), and only a small proportion of trials (5/102, 4.9%) launched exclusively in LMICs excluding China and European middle-income countries. For most studies, aspects of trial design and trial documentation (including study protocols and analysis plans) were not publicly accessible.Conclusion Unlike high-income countries, where several hundreds of master protocols are ongoing or completed, there is limited use of master protocols in LMICs, partly owing to low penetration of precision medicine research and limited clinical trial infrastructure in most LMICs. The evidence presented here creates a case for supporting precision medicine initiatives in LMICs (especially Africa) and training and capacity building initiatives focused on innovative clinical trial designs like master protocols, especially in therapeutic areas outside oncology.